(untitled) (Journal of Science and Technology Research, 2024)
Blastocystis is a widespread protozoan known to induce digestive disorders in humans and animals, including cattle globally. The parasite exhibits a significant amount of genetic variability and is divided into 42 recognized subtypes (STs) in mammals and birds. Sixteen of these subtypes are identified in cattle and 14 are zoonotic. This study explored the distribution and genetic variations of Blastocystis and its zoonotic potential in dairy cattle. Two hundred fresh fecal samples were collected from smallholder dairy calves (aged <6 months) in two milk pocket areas of Bangladesh: Sirajganj (n=100) and Pabna (n=100). A molecular study based on PCR assay targeting the small subunit ribosomal RNA (SSU rRNA) gene was employed to screen and subtype the parasite in the fecal samples. Analyses revealed Blastocystis among 10% of the cattle, with 8% positive cases in samples from Sirajganj and 12% in samples from Pabna. Various factors including sex, age, breed groups, and fecal consistency were considered, although these were found to be statistically insignificant. Out of the 20 positive Blastocystis isolates, only three subtypes, namely ST10, ST21, and ST26, were identified where subtype ST10 was the most prevalent. Notably, no zoonotic subtypes were detected in the fecal samples, suggesting a lack of zoonotic significance. The findings provide insights into the molecular epidemiology of Blastocystis infection in cattle, indicating its low genetic diversity in the study areas. Further research is needed to determine the exact frequency and genetic composition of Blastocystis and its zoonotic potential in cattle in Bangladesh. J. of Sci. and Tech. Res. 6(1): 13-20, 2024